Parametic study on ductility of RC beams strengthened with external reinforcement - Wong, Kien Kuok. (Universiti Malaysia Sarawak, UNIMAS, 2002)
Bonding of steel plates or other advanced composite materials to the tension face of the beam is one of the methods for strengthening these deteriorated concrete structures. This may increase the strength and stiffness of the concrete structures nevertheless the corresponding ductility of reinforced concrete beam is being affected by increasing the strength of the beam using externally bonded steel plates.